Oral epidemiological profile of patients attending public oral health services in Haut Sassandra region, in Côte d'Ivoire - Guanga David Meless; Jean-Claude Guinan; Abou Dramane Sangaré; Koffi Syvain N'Guessan; Koffi Lazare Kouakou; Viviane Da-Danho; Atta Sebastien Datté; N'Zébo Marcellin Nouaman; Asse Marie Anita Amangoua; Mamadou Samba; Ramata Bakayoko-Ly (AOSIS, 2020)
The objective of this cross-sectional study was to determine the type of care that can be achieved and the epidemiological profile of patients attending the 3 public dental practices in the Haut-Sassandra region, in Côte d'Ivoire. The data collection concerned socio-demographic characteristics, reason for consultation, oral hygiene, dental condition, malocclusions and the availability of equipment for the performance of procedures. The 400 patients observed (51.5% male) were aged 16.0 to 86.0 years (mean=35.5 years; SD=13.1 years). The main reasons for consultation were pain (91.5%) and aesthetics (23.5%). Oral hygiene was insufficient for 36.8% of subjects. Oral conditions were malocclusions (12.8%), caries (98.7%) and edentulous (65.7%) with only 11.8% with prosthesis. The average DMFT index was 9.3. Only extractions and resin attached prostheses were possible in all 3 health facilities. Preventive dentistry (sealent, fluoridation), dentofacial orthopedics and implantology were not available in any dental practice. The most frequently performed acts were extractions (74.5%). The results of this study highlight the need for oral health planning with service equipment and awareness among populations who shouldn't wait until they are in pain to consult.